Typical mistakes in urban landscape drawing - Markitantova Tatiana O. (Архитектон, 2025)
The article reviews problems that students of architecture and restoration face in drawing urban landscapes using as an example the central districts of St. Petersburg. The most typical mistakes in drawing urban environments are: loss of authenticity of buildings; violation of scale; perspective distortions, including accelerated perspective resulting in strong foreshortening distortions, and, as a consequence, violations of building heights and ratios of building heights to canal and street width. Particular attention is paid to the display of depth in the drawing of the city square. Consideration is given to problems of using central projection on plane in depicting large urban objects, and to differences between drawings performed from life and from imagination, and perspective images obtained geometrically. The principle of depicting urban spaces is analyzed using the artistic heritage of past masters as an example. Constructive, structural features of spatial landscape organization are revealed, which help to apply this knowledge in practical visual activities. Student with are analyzed for typical errors.